FATAL GRIEVANCES forecasting and preventing active killer threats in school, campus, and... workplace settings. - Vecchi, Gregory M.; Markey, Mary Ann, 1949-; Daniels, Jeffrey A., 1965- ([S.l.] : ROUTLEDGE, 2023)
Active killer attacks frequently dominate the headlines with stories of seemingly random mass killings in school, campus, and workplace settings. Nearly all of the attacks are over before the police can respond, leaving unanswered questions as to why these attacks happen and what can be done to prevent them. Fatal Grievances: Forecasting and Preventing Active Killer Threats in School, Campus, and Workplace Settings takes a proactive view of active killer threat management and resolution to prevent the attack before it occurs. Drawing from established threat assessment, behavioral analysis, and law enforcement negotiation theory and practice, the book presents models and methods designed to forecast and prevent an active killer attack through the process of identification, assessment, and engagement. This approach begins with definitions and orientations to violence, the importance of the primacy of focusing on direct behaviors of planned lethal violence over other more indirect behaviors, understanding how to identify a fatal grievance and that only fatal grievances result in planned lethal violence, the importance of understanding the process of crisis intervention as the key to eliminating the fatal grievance and the motivation to kill, and the use of time-series predictive behavioral threat forecasting methods to prevent an active killer attack. Case studies from within the United States (US) and abroad support this unique approach to threat assessment and make the concepts and principles accessible to professionals working in the fields of education, human resources, and security.
OCLC-licensed vendor bibliographic record.
Keywords: Mass shootings -- United States -- Prevention; Mass shootings -- United States -- Forecasting; Violent crimes -- United States; SOCIAL SCIENCE / Criminology